DETERMINANTS OF THE EFFECTIVENESS OF SHARIA BANK CREDIT DISTRIBUTION IN NORTH SUMATRA 2020-2022 - M Syafii; Syech Suhaimi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The bank's ability to provide liquidity for several sharia banks is influenced by the interest rates set, where in sharia banks the interest rates set are included in a profit sharing ratio, where if the profit sharing ratio is greater than it should be, it will affect customer payments, where the customer does not It is permissible to increase the existing ratio, because it can reduce the bank's ability to obtain a rate of return of funds from payment of obligations, so that by distributing the appropriate ratio the customer will not receive profit sharing payments that are detrimental to him and enable the customer to pay well. Meanwhile, the level of profit sharing for the 2020-2022 payment period tends to be inconsistent with what customers should receive when carrying out a murabahah financing agreement . Customers will tend not to be able to increase their obligation payments on time, which will impact the bank's ability to increase liquidity or the FDR value will decrease and impact the ability of sharia banks to finance murabahah financing products . The aim of this research is to find out and understand the extent to which the amount of credit disbursed by Islamic banks, the level of profit sharing (nisbah), capital adequacy ratio , operational costs per operating income (BOPO), return on equity (ROE) influence the bank's ability to increasing the amount of funds or liquidity in distributing credit (FDR). This research is quantitative descriptive research using a survey method. The population and sample in this research are 33 sharia banks in North Sumatra which are experiencing several problems increasing their ability to provide funds for the credit distribution process (FDR). The data analysis technique used is using panel data regression. The research results state that partially only the variable amount of murabahah financing, CAR/KPMM and ROE have a positive and significant effect on the FDR of sharia banks in North Sumatra, while the variables of profit sharing level and BOPO have a negative effect on the FDR of sharia banks in North Sumatra. Simultaneously, the variable amount of murabahah financing , the profit sharing level variable, the CAR/KPMM, BOPO, ROE variables have a positive and significant effect on the FDR variable of several sharia banks in North Sumatra